Using Clustering Technique in Teaching Writing - Tenia Ramalia; Nirna Nirmala (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2019)
AbstractWriting is categorized as a productive skill which means learners doing these to produce language. It is the process of developing the idea, arranging the words becoming a good writing. As a productive skill, writing is considered as a complex one. The following article tries to discuss the technique which can be used in teaching writing, The Clustering Technique. The aim of this study is to discuss the use of clustering technique in teaching writing based on the teories or previous researches. Based on the literature review of the previous research and expert opinion, it is found that clustering technique is very effective to be used in teaching writing. This technique allows the students to generate their ideas easily, group them correctly, and develop them into an organized paragraph. The method of this research is a literature review. The result shows that this technique can improve students writing skill. It helps students develop their idea before they writing. Besides, they also feel motivated and fun in writing.Keywords: Clustering technique, Teaching, Writing skill. AbstrakMenulis merupakan keterampilan produktif dimana peserta didik melakukannya untuk menghasilkan bahasa. Menulis adalah proses mengembangkan ide, mengatur kata-kata menjadi tulisan yang bagus. Sebagai keterampilan produktif, menulis dianggap sebagai keterampilan yang kompleks. Artikel berikut mencoba membahas teknik yang dapat digunakan dalam pengajaran menulis, The Clustering Technique. Tujuan dari penelitian ini adalah untuk membahas penggunaan teknik pengelompokan dalam pengajaran menulis berdasarkan cerita atau penelitian sebelumnya. Berdasarkan tinjauan pustaka dari penelitian sebelumnya dan pendapat ahli, ditemukan bahwa teknik clustering sangat efektif untuk digunakan dalam pengajaran menulis. Teknik ini memungkinkan siswa untuk menghasilkan ide-ide mereka dengan mudah, mengelompokkannya dengan benar, dan mengembangkannya menjadi paragraf yang terorganisir. Metode penelitian ini adalah tinjauan pustaka. Hasilnya menunjukkan bahwa teknik ini dapat meningkatkan keterampilan menulis siswa. Ini membantu siswa mengembangkan ide mereka sebelum mereka menulis. Selain itu, mereka juga merasa termotivasi dan senang dalam menulis.Kata kunci: Clustering, pengajaran, keterampilan menulis.